Impulsivity and Its Relationship With Lisdexamfetamine Dimesylate Treatment in Binge Eating Disorder - Griffiths, Kristi R.; Aparício, Leonor; Braund, Taylor A.; Yang, Jenny; Harvie, Grace; Harris, Anthony; Hay, Phillipa J.; Touyz, Stephen; Kohn, Michael R. (Frontiers in Psychology, 2021)
High trait impulsivity is thought to contribute to the sense of loss of control over eating and impulses to binge eat experienced by those with Binge Eating Disorder (BED). Lisdexamfetamine Dimesylate (LDX), a drug approved for treatment of moderate to severe BED, has been shown to decrease impulsive features of BED. However, the relationship between LDX-related reductions of binge eating (BE) episodes and impulsivity has not yet been explored. Forty-one adults aged 18-40 years with moderate to severe BED completed questionnaires and tasks assessing impulsivity at baseline and after 8 weeks of 50-70mg of LDX. Twenty age-matched healthy controls were also assessed at 2 timepoints for normative comparison. Data were analysed using linear mixed models. BED participants exhibited increased self-reported motor, non-planning, cognitive and food-related impulsivity relative to controls but no differences in objective task-based measures of impulsivity. Food-related and non-planning impulsivity were significantly reduced by LDX, but not to normative levels. Individuals with higher baseline levels of motor and non-planning impulsivity, and loss of control over eating scores experienced the greatest reduction in BE frequency after 8 weeks of LDX. Further, there were significant associations between the degree to which subjective loss of control over eating, non-planning impulsivity and BE eating frequency reduced after 8 weeks of LDX. These data suggest that specific subjective measures of impulsivity may be able to predict who will have the greatest benefit from LDX treatment, and that reductions in binge eating frequency may be moderated by concurrent reductions in non-planning impulsivity.